Pengaruh Tax Avoidance Terhadap Nilai Perusahaan Dengan Corporate Governance Sebagai Variabel Pemoderasi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Nur Azija Fajriah Tulhijrah Kelilauw; Aaron M. A Simanjuntak; Cornelia D. Matani (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This study aims to determine the effect of tax avoidance on firm value with corporate governance proxied by audit quality as a moderating variable. This research was conducted on the Consumer Goods Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Samples were collected using purposive sampling technique so that the number of samples obtained were 23 companies and 115 financial statements were obtained. This study uses linear regression analysis data testing and moderate regression analysis (MRA). The results show that Tax Avoidance has an effect on firm value and that Corporate Governance as proxied by audit quality is able to moderate the effect of tax avoidance on firm value.